2021
DOI: 10.37962/jpps.v9i1.476
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice Regarding Herbal Medicine Among Medical Students in Saudi Arabia

Abstract: Background: Herbal medicine is becoming increasingly popular among the general population.  Before consulting a medical practitioner, patients already try home remedies. Therefore, it becomes more pertinent that the medical students as future doctors, must possess some knowledge of the herbal medicine. In Saudi Arabia, no study has yet evaluated this aspect in medical students. Methods: A cross-sectional study was performed with 240 medical students at a Health Sciences University. The survey questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Similarly, Bhat et al reported that most of the respondents in the Udupi region lacked an understanding of medicine dosage, duration, adverse effects, and interactions [17]. Medical students in Saudi Arabia were found to be unaware of some crucial aspects of herbal medications, according to Zaidi et al [18]. [21].…”
Section: Knowledge Of Herbal Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Bhat et al reported that most of the respondents in the Udupi region lacked an understanding of medicine dosage, duration, adverse effects, and interactions [17]. Medical students in Saudi Arabia were found to be unaware of some crucial aspects of herbal medications, according to Zaidi et al [18]. [21].…”
Section: Knowledge Of Herbal Medicinementioning
confidence: 99%
“…Furthermore, El-Olemy et al stated that 46% of respondents in their study feel that complementary and traditional medicine is safe and medically effective, with 87% of those who have previously used complementary and traditional medicine have not experienced any complications [16]. According to Zaidi et al, most Saudi Arabian medical students felt that herbal medicines are beneficial in maintaining and promoting health (51.3%) and treating illness (52.9%) [18].…”
Section: Attitudes Toward Herbal Medicinementioning
confidence: 99%